Magnetically altered phase stability in Fe-based alloys: Modeling and database development. (December 2021) - Murdoch, Heather; Giri, Anit; Field, Daniel; Hernández-Rivera, Efraín; Guziewski, Matthew
Abstract: Processing of materials under an externally applied magnetic field could enable exploitation of broader processing spaces, affecting the relative stability of phases. To properly predict how a material will react to an applied field, the magnetic properties must be incorporated into the free energy calculations. Previous works assumed alloy composition played a negligible effect on the magnetization term; however, this assumption is not valid for all systems. Here, we assess twelve binary iron systems to quantify the shifts of magnetic moment and Curie temperature with respect to alloy content. Descriptive magnetic property equations for these binary systems were assessed in conjunction with experimental data and prior descriptions obtained from literature. To showcase the impact of using the compositionally dependent magnetic property predictions, the austenite loops for Fe–Si and Fe–Mo were re-calculated under an applied magnetic field. Further, the magnetic property data summarized herein can also be used for future assessments or re-assessments of the iron alloy systems reported, in addition to the current goal of processing under magnetic fields.